PENTINGNYA KOLABORASI ORANG TUA DAN SEKOLAH DALAM GERAKAN ANTI PERUNDUNGAN - Hendarty, Tety; Wasliman, Iim; Nurhasanah, Siti Sarah; Wasliman, Eva Dianawati; Harliyani, Dian (STKIP PGRI Situbondo, 2024)
Bullying is a phenomena that affects children in their social contexts, including their families, communities, and schools, even in kindergarten. This is what motivated the conduct of this study. It is crucial that early childhood educators and parents work together to stop bullying. The following are the research objectives: (1) Describe how parents and schools work together to manage the anti-bullying campaign; (2) List the elements that encourage and obstruct parent and school collaboration in the anti-bullying movement. Case studies were employed in this qualitative research project. Data were gathered through observations, documentation, and interviews. The findings of the study demonstrate how crucial it is for parents and schools to work together in anti-bullying campaigns in order to stop bullying in schools. Schools must keep pushing parents to get involved in anti-bullying initiatives, particularly by reaching out to them with information about bullying. Bullying in schools can be decreased via effective collaboration between parents and schools. Together, parents and schools can provide a secure and encouraging learning environment for every student. Increased communication, active participation, understanding, acknowledging the role of parents, and an integrated strategy between schools and parents can all help achieve this.